2009
DOI: 10.1152/ajpcell.00166.2009
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced internalization and downregulation of gonadotropin-releasing hormone receptors

Abstract: Gonadotropin-releasing hormone (GnRH) acts via seven transmembrane receptors to stimulate gonadotropin secretion. Sustained stimulation desensitizes GnRH receptor (GnRHR)-mediated gonadotropin secretion, and this underlies agonist use in hormone-dependent cancers. Since type I mammalian GnRHR do not desensitize, agonist-induced internalization and downregulation may underlie desensitization of GnRH-stimulated gonadotropin secretion; however, research focus has recently shifted to anterograde trafficking, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…Following stimulation with agonists, G-protein coupled receptors are internalized (Yu et al, 1993; Lefkowitz, 1998; Finch et al, 2009). Receptor internalization serves not only to turn off persistent receptor signaling but it also allows cells to regulate sensitivity to subsequent agonist exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Following stimulation with agonists, G-protein coupled receptors are internalized (Yu et al, 1993; Lefkowitz, 1998; Finch et al, 2009). Receptor internalization serves not only to turn off persistent receptor signaling but it also allows cells to regulate sensitivity to subsequent agonist exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of a C-terminal tail implies that the GnRHR may be resistant to rapid desensitization and internalization, and this has been confirmed experimentally for this receptor in a variety of settings [283;291;291;292]. In addition, numerous studies have demonstrated rapid desensitization and internalization of chimeric receptors in which the C-terminal tail of various GPCRs was fused to the C-terminus of the mammalian type I GnRHR [29;70;98;103;104;107;209;283]. Collectively, these results establish a causal link between the absence of the C-terminal tail and the delayed internalization kinetics of the type I GnRHR.…”
Section: Molecular Basis Of the Response Of The Gonadotrope To Gnrhmentioning
confidence: 97%
“…Continuous stimulation of the agonist together with the feedback of the sex hormones cause the down-regulation of FSH and LH production, preventing the maturation of follicles and the subsequent ovulation, inhibiting the secretion of E2 and P4. The downstream signalling of the receptors is complex and the exact mechanism involved leading to the desensitisation of pituitary response is still very much under debate, however, agonist-induced internalisation and down-regulation of GnRH receptors have been observed [12,33]. Furthermore, continuous stimulation of GnRH is reported to reduce MAPK (mitogen-activated protein kinases) activities suppressing the production of FSH and LH and, at the same time, affecting the synthesis of GnRH receptors, possibly paralysing pituitary's response to GnRH stimulation [27,28].…”
Section: Modelling Gnrh Treatment and Receptor Down-regulationmentioning
confidence: 99%